Evaluación de desempeño del personal del Centro de Distribución Topsy Manabí para el mejoramiento de las competencias laborales - Bravo Intriago, Jessica Andrea (2021)
The development of this research was aimed at evaluating the performance of the Topsy Distribution Center staff, in order to achieve the improvement of labor competencies, for this purpose, it was necessary to structure the methodological procedure, through three basic development phases, being necessary to apply a bibliographic and field type research, since it consisted of studying the unit of analysis at the scene, supported by analysis and synthesis as basic techniques, for the application of tools such as the survey and interview , in the information gathering stage; While in the stage of processing, analysis and diagnosis of the data collected, statistical software such as SPSS, Microsoft Office Excel, the Ishikawa diagram and the 5w + 1h matrix were used. Key procedure that allowed the identification of a total of 14 labor competencies for measurement, of which customer orientation presents a high level of performance, while 12 show a medium achievement and only the structure and organization competence reflected a low level. corresponding to 63%; concluding by means of the study, the need to apply permanent performance evaluations, in order to develop the competencies of the personnel and bring the indicators that integrate them from low or medium to high or developed weights.